ANALYSIS OF TEACHER SATISFACTION WITH ONLINE LEARNING DURING THE COVID-19 PANDEMIC AT SDN 054905 LANGKAT REGENCY - Saiful Bahri; Nila Lestari; Dalyanto Dalyanto (Sensei International Journal of Education and Linguistic, 2022)
This research is motivated by the existence of an online learning policy for educational units caused by the Covid-19 pandemic which is a disaster for the whole world. The purpose of this study was to determine teacher satisfaction with online learning policies, especially teachers at SDN 054905 Langkat Regency. This type of research is a qualitative research using descriptive qualitative analysis techniques. The subjects in this study were all teachers at SDN 054905 Langkat Regency. The object of this research is to analyze the level of teacher satisfaction with online learning. Data collection tools used by researchers are interview sheets, and teacher satisfaction questionnaires/questionnaires, documentation. The results of this study were concluded that 70% of teachers stated "Not Satisfied" with online learning and another 30% stated "Satisfied". This assumption is related to external factors such as internet network facilities and the number of students who do not have smartphones as learning facilities, and internal factors are the lack of teacher skills in online learning.